2000
DOI: 10.1128/jb.182.11.3055-3062.2000
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation of Bacillus subtilis ς D -Dependent Gene Expression

Abstract: In work by others, CodY has been implicated in the nutritional repression of several genes. Analysis of a codY mutant bearing a hag-lacZ reporter revealed that flagellin expression is released from nutritional repression in this strain, whereas mutations in the transition state preventor genes abrB, hpr, and sinR failed to elicit a similar effect during growth in complex medium. Therefore, the CodY protein appears to be the physiologically relevant regulator of hag nutritional repression in B. subtilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…The transcriptional profiling experiments offer several hints why such a large number of B. subtilis genes associated with chemotaxis and cell motility are so strongly repressed under high-saline environmental conditions. The GTP-binding protein CodY, which functions as a nutrition-responsive repressor in B. subtilis (56), appears to repress flagellin gene expression in response to the availability of amino acids (44). CodY has been shown to bind specifically to DNA fragments containing the promoters for both the fla/che operon and the hag gene (1,44), and we found that expression of codY increased by a factor of approximately 2 in B. subtilis cells propagated at high salinity (see supplemental material).…”
Section: Vol 185 2003 High-salinity Adaptation Of B Subtilis 6365mentioning
confidence: 99%
See 1 more Smart Citation
“…The transcriptional profiling experiments offer several hints why such a large number of B. subtilis genes associated with chemotaxis and cell motility are so strongly repressed under high-saline environmental conditions. The GTP-binding protein CodY, which functions as a nutrition-responsive repressor in B. subtilis (56), appears to repress flagellin gene expression in response to the availability of amino acids (44). CodY has been shown to bind specifically to DNA fragments containing the promoters for both the fla/che operon and the hag gene (1,44), and we found that expression of codY increased by a factor of approximately 2 in B. subtilis cells propagated at high salinity (see supplemental material).…”
Section: Vol 185 2003 High-salinity Adaptation Of B Subtilis 6365mentioning
confidence: 99%
“…The GTP-binding protein CodY, which functions as a nutrition-responsive repressor in B. subtilis (56), appears to repress flagellin gene expression in response to the availability of amino acids (44). CodY has been shown to bind specifically to DNA fragments containing the promoters for both the fla/che operon and the hag gene (1,44), and we found that expression of codY increased by a factor of approximately 2 in B. subtilis cells propagated at high salinity (see supplemental material). CodY-mediated reduction of fla/che operon expression might also partially account for the threefold reduction in sigD transcription observed at high versus low salinity (Table 2).…”
Section: Vol 185 2003 High-salinity Adaptation Of B Subtilis 6365mentioning
confidence: 99%
“…It follows that in cases of nutrient limitation leading to a drop in GTP in the cell, CodY repression is alleviated, allowing the expression of many genes involved in cell adaptation to this poorer environmental condition. Many CodY-dependent genes are also regulated by additional mechanisms, allowing their control in response to other environmental factors (Brandenburg et al, 2002;Debarbouille et al, 1999;Ferson et al, 1996;Kim et al, 2003;Mader et al, 2004;Mirel et al, 2000;Nakano et al, 1991;Oda et al, 2000;Ogura et al, 2001;Wray et al, 1997;Yoshida et al, 2003). In B. subtilis, CodY has been shown to directly interact with, in addition to GTP, BCAA, in particular isoleucine (Shivers & Sonenshein, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The role exerted by this global regulator can be compared to that of CRP in E. coli (Moreno et al, 2001). CodY represses the expression of a wide variety of genes involved in macromolecular degradation, nutrient transport, amino acid catabolism, branchedchain amino acid (BCAA) biosynthesis, genetic competence, antibiotic synthesis, motility and chemotaxis (Bergara et al, 2003;Debarbouille et al, 1999;Ferson et al, 1996;Fisher et al, 1996;Inaoka & Ochi, 2002;Inaoka et al, 2003;Kim et al, 2003;Lazazzera et al, 1999;Mirel et al, 2000;Molle et al, 2003;Serror & Sonenshein, 1996a, b;Shivers & Sonenshein, 2004;Slack et al, 1995;Wray et al, 1997). In controlling expression of these late-exponential-phase and early-stationary-phase genes, the regulation by CodY allows cells to adapt to general nutrient limitation (Molle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…At high internal CSF concentrations, CSF inhibits competence and promotes spore development. Specifically, CSF inhibits ComS, reducing transcription of competence genes and promoting sporulation instead (Lazazzera et al, 1997;Solomon, 1995;Perego and Hoch, 1996;Mirel et al, 2000;Stephens, 1998).…”
Section: Microbially Synthesized Bioactive Peptides By the Genus Bacimentioning
confidence: 99%